2014
DOI: 10.15713/ins.jcri.2
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the clinical features of 530 cases of reactive lesions of oral cavity

Abstract: Background: Most common localized reactive lesions of oral cavity are focal fibrous hyperplasia, pyogenic granuloma (PG), irritational fibroma, peripheral giant cell granuloma (PGCG), peripheral ossifying fibroma (POF), fibro-epithelial hyperplasia/polyp, inflammatory fibrous hyperplasia and inflammatory gingival hyperplasia. Clinically, these reactive lesions often present diagnostic challenges because they mimic different groups of pathologic processes. The aim of this paper is to document the occurrence, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Ala Aghbali et al13, in their study of 197 cases of reactive hyperplastic lesions reported a mean age of 37.68 ± 18.97 years which was similar to our mean age of 37.7±21.1 yrs. Other studies have reported higher mean ages (Between 40–45 years) for oral RHLs15,16. It is also important to highlight that the highest prevalence of the lesion in this study was found in the age group 9–29 years old; while the oldest age groups 70–89 years and >90 years, had the lowest prevalence.…”
Section: Discussionmentioning
confidence: 86%
“…Ala Aghbali et al13, in their study of 197 cases of reactive hyperplastic lesions reported a mean age of 37.68 ± 18.97 years which was similar to our mean age of 37.7±21.1 yrs. Other studies have reported higher mean ages (Between 40–45 years) for oral RHLs15,16. It is also important to highlight that the highest prevalence of the lesion in this study was found in the age group 9–29 years old; while the oldest age groups 70–89 years and >90 years, had the lowest prevalence.…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, the most common site recorded was buccal mucosa at the line of occlusion and similar finding is noted by Hunasgi et al . [ 4 ] [ Figure 1 ]. Clinically, FIBs mimic various lesions such as giant cell FIB, neuro FIB, PGCG and can be differentiated from the conventional FIBs with the help of histologic appearance.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Even though the lesion is benign, it has a tendency of recurrence with incomplete excision and inability to remove local irritants. [ 4 ] The usage of CO 2 laser is preferred over surgical excision with minimal recurrence rate followed by maintenance of oral hygiene and regular follow-ups. [ 5 ] This study reviews, analyzes, and compares the demographic data, histopathological features and discusses the treatment and prognosis of RLs.…”
Section: Introductionmentioning
confidence: 99%
“…The distinction is made based on careful examination of the tissue mass, to determine if it is connected to the pulp or gingiva. In a study on 530 cases of focal reactive lesions of the oral cavity Hunagsi et al 8 found that inflammatory gingival hyperplasia was the most prevalent lesion with 51% of the cases. The extent of the root curvature is one of the most important variables that could lead to instrument fracture during endodontic treatment.…”
Section: Discussionmentioning
confidence: 99%